Tahfiz Online: Sarana Menghafal Alquran Secara Online - Bobi Erno Rusadi (UMSU, 2020)
The development of technology that continues to grow makes it easier for everyone to learn. Likewise with learning the Quran especially memorizing the Quran. Busyness experienced is not a reason not to memorize the Qura. Various online tools and applications can be used to memorize the Quran, one of which is the tahfiz onlineprogram. Tahfiz Online is one of the means by which someone memorizes the Quran online by using whatsapp media. This study aims to describe the process of learning memorizing Quran which is carried out by the tahfiz online program which starts from the process of recruiting new students, the learning process, and evaluating the learning which is carried out by the Tahfiz Online program. The research method used is qualitative research with data collection methods of observation and interviews. The results of this study describe that new student recruitment activities carried out by the online tahfiz program are carried out with Alquran reading tests conducted by students by sending voice notes to the teacher (musyrif). Furthermore, in tahfiz learning activities, each student carries out two activities namely ziyadah (adding new memorize) and murajaah (repetition). Ziyadah activities are carried out every Monday to Friday by sending voice notes in the group that will be corrected by each musyrif. Whereas the deliberate activities carried out on Saturdays and Sundays are carried out in pairs. Evaluation of learning are carried out every week with aspects of assessment including daily memorization values, activeness in groups, etiquette, and ending with a final exam with the term IMTAK (Imtihan Akbar).